NEWS DIFFUSION ACROSS SOCIAL MEDIA PLATFORMS - Karnowski, Veronika; Keyling, Till; Leiner, Dominik (AoIR Selected Papers of Internet Research, 2014)
In 2013 73% of US online adults used at least one social networking site, most of them Facebook (Duggan & Smith, 2013). Scholarly research in communication so far concentrated on four topics brought about by this trend: impression management and friendship performance, network and network structures, bridging online and offline networks, and privacy (Zhang & Leung, 2014). We want to point scholarly interest to another topic: the mechanics of dissemination of news content via social media. In 2013 30% of US adults actually got news content from Facebook (Mitchell, Holcomb, & Page, 2013); a trend still strongly correlated to certain sociodemographic characteristics of users, but speculated to be of ever growing importance (Glynn, Huge, & Hoffman, 2012). What is the interplay of sharing patterns of online news content across Facebook and Twitter: 1) in general? 2) with regard to characteristics of the news content? To answer these questions, we developed a large-scale driven methodical framework which matches standardized information on news articles with the available indicators of interest on Facebook and Twitter. Our analysis covers the period from September 10, 2012 to November 1, 2012, based on the following news outlets: Spiegel Online, Bild online, Süddeutsche Zeitung (SZ), New York Times, CNN, and Fox News.